The Prevalence of Internet User Addiction among Communication Science Students, Djuanda University, Bogor - Ruli Ananda Putri; Yulianti; Aulia Adhinia Febriyanti; Khonsa Khoulah; Luthfiah Hayati Sigalingging; Siti Zulfa Fauziah; Ali Alamsyah Kusumadinata (Formosa Journal of Science and Technology, 2023)
As the advancement of internet technology has a big impact on humans. Almost all sectors of life use the internet. Internet addiction is a widespread phenomenon, especially among young people, one of which is university students. Internet addiction is the attitude of someone who is fixated on an electronic device that has an internet connection. The purpose of this study was to find out how much the prevalence of internet users was among Djuanda University Communication Science students. The research approach uses descriptive quantitative methods, which is a method used by taking a sample of a population using a non-probability sampling technique. This data collection was taken from a questionnaire via google form to 50 Djuanda University students. The results show that internet addiction does not worry users. But there are other factors such as entertainment.